Impacts of liquidity ratios on profitability of commercial bank in Malaysia / Zulfikar Zakaria - Zakaria, Zulfikar (2012)
The present study aims to reveal the relationship between liquidity and profitability so that every bank has to maintain this relationship while conducting day to day operation. There are two objectives for the study that will give some guidelines in order to do the research effectively which is to examine the relationship that exists between liquidity ratios with profitability and also to determine which variables have the strongest relationship toward profitability. The study will be done on current ratio, liquid ratio, and loans to assets ratio towards return on assets. For this purpose, seven commercial banks in Malaysia had been chosen